2015
DOI: 10.1371/journal.pone.0125311
|View full text |Cite
|
Sign up to set email alerts
|

miR-20a Inhibits TCR-Mediated Signaling and Cytokine Production in Human Naïve CD4+ T Cells

Abstract: Upon TCR stimulation by peptide-MHC complexes, CD4+ T cells undergo activation and proliferation. This process will ultimately culminate in T-cell differentiation and the acquisition of effector functions. The production of specific cytokines by differentiated CD4+ T cells is crucial for the generation of the appropriate immune response. Altered CD4+ T-cell activation and cytokine production result in chronic inflammatory conditions and autoimmune disorders. miRNAs have been shown to be important regulators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Asterisks indicate whether there were significant differences among the groups. *P < 0.05; **P < 0.01. www.nature.com/scientificreports www.nature.com/scientificreports/ was detected; (iii) and previously published data regarding the miRNAs profile in decompensated cirrhosis 17,18 , inflammation 19,20 , and sepsis [21][22][23] .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Asterisks indicate whether there were significant differences among the groups. *P < 0.05; **P < 0.01. www.nature.com/scientificreports www.nature.com/scientificreports/ was detected; (iii) and previously published data regarding the miRNAs profile in decompensated cirrhosis 17,18 , inflammation 19,20 , and sepsis [21][22][23] .…”
Section: Discussionmentioning
confidence: 77%
“…Based on the magnitude of expression difference between patients with and without ACLF in the microarray analysis and in literature reports [17][18][19][20][21][22][23] miRNAs miR-106b-5p, miR-126-3p, miR-20a-5p, miR-223-3p, and miR-25-3p were selected to be further validated by RT-qPCR. Some miRNAs that had high FC values such as let-7a-5p and let-7g-5p were not detected in most microarray samples and were therefore not included in the validation step.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, miR-20a is a member of the miR-17-92 cluster which has been demonstrated to play important roles in various biological processes including oncogenicity (Wang Z. et al, 2015 ), immune regulation (Cox et al, 2010 ), and disease progression (Sasaki et al, 2010 ). It is reported that miR-20a inhibits TCR-mediated signaling and cytokine production in human naïve CD4 + T cells (Reddycherla et al, 2015 ). Zhu et al have demonstrated that a panel of miRNAs including miR-20a, miR-17, and miR-106a can regulate macrophage inflammatory responses by targeting signal-regulatory protein α (Zhu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the upregulation of miR-21 could be sustained by the contextual downregulation of miR-20a that could contribute to the lack of an anti-inflammatory property [ 22 ].…”
Section: Discussionmentioning
confidence: 99%